SIJUNZI DECOCTION DEMOLITION PARTIES INHIBIT PROLIFERATION AND INDUCE APOPTOSIS OF HUMAN GASTRIC CANCER BGC823 SIDE POPULATION - Qian, Jun; Xie, Hui; Guo, Chenxu; Sun, Rui; Su, Lin; Jia, Jianguang; Jin, Xin; Yu, Dajun; Li, Jing (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Comprehensive treatment combining with Chinese medicine has become the main therapeutic regimen of gastric cancer. Previous evidence demonstrated SD can enhance the effect of chemotherapy in advanced cancer, especially in gastric cancer. In order to investigate the anticancer mechanism of SD in gastric cancer, we observed the effects of SD parties (Ginseng, Atractylodes, Poria, Licorice) on proliferation and apoptosis of SP of human gastric cancer BGC-823. Materials and Methods: 1. BGC-823 side population cells were sorted through flow cytometry. 2. To detect the changes of proliferation of SP and NSP before and after the intervention of serum containing SD parties using cck-8 method. 3. To detect the changes of cell cycle and apoptosis of SP and NSP before and after the intervention of serum containing SD parties through flow cytometry. 4. To detect the effects of serum containing SD parties on apoptosis-related proteins Bax and Bcl-2 of SP and NSP before and after the intervention by western-blot. Results: It was found that four demolition parties serum treatments inhibited cell proliferation in a time-dependent manner. Compared with the control group (normal saline treatment), there were increase in G1/G0 phase population of SP and NSP, and decrease in G2/M and S phase population (P<0.05). Meanwhile, we found G1/G0 arrest induced by four demolition parties serum which was followed by apoptosis in a time-dependent manner. The apoptosis rate of drug serum treatment group was higher than the control group (P<0.05), and the apoptosis rate of 48 h treatment was higher than 24 h treatment (P<0.05). The expression of Bax protein of SP and NSP was higher than the control group in a time-dependent manner. The expression of Bcl-2 protein of SP and NSP was lower than the control group in a time-dependent manner. Conclusion: The serum of four demolition parties of SD can inhibit the proliferation of SP of BGC-823 cell lines through G1/G0 phase arrest and followed by apoptosis which involves the up-regulation of Bax and the down-regulation of Bcl-2.